2018
DOI: 10.1016/j.amepre.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Activity Assessments and Interventions Using Technology in Older Adults

Abstract: This paper reports on the findings and recommendations specific to older adults from the "Tech Summit: Innovative Tools for Assessing Diet and Physical Activity for Health Promotion" forum organized by the North American branch of the International Life Sciences Institute. The summit aimed to investigate current and emerging challenges related to improving energy balance behavior assessment and intervention via technology. The current manuscript focuses on how novel technologies are applied in older adult popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 104 publications
2
35
0
1
Order By: Relevance
“…A survey of robots that support the independent living of older adults found that there has been a rapid evolution of technology in this area, and that most studies to date have been conducted in laboratories and hospital settings [30]. Another review paper found evidence that socially assistive robots can enhance the well-being of older adults while reducing the workload for caregivers [31], and other work suggests that older adults can adopt new technologies to support better diet and physical activity practices given proper training and guidance [32]. Past ethnographic research provides best practices for introducing a robot into an assisted living facility while also presenting evidence that older adults accepted the robot into the community [33].…”
Section: Related Workmentioning
confidence: 99%
“…A survey of robots that support the independent living of older adults found that there has been a rapid evolution of technology in this area, and that most studies to date have been conducted in laboratories and hospital settings [30]. Another review paper found evidence that socially assistive robots can enhance the well-being of older adults while reducing the workload for caregivers [31], and other work suggests that older adults can adopt new technologies to support better diet and physical activity practices given proper training and guidance [32]. Past ethnographic research provides best practices for introducing a robot into an assisted living facility while also presenting evidence that older adults accepted the robot into the community [33].…”
Section: Related Workmentioning
confidence: 99%
“…The forum resulted in expert review papers on technology innovations in three age cohorts that are published concurrently with this commentary: "Advances and Controversies in Diet and Physical Activity Measurement in Youth" 12 ; "Dietary Intake and Physical Activity Assessment: Current Tools, Techniques, and Technologies for Use in Adult Populations" 13 ; and "Diet and Physical Activity Assessment and Interventions Using Technology in Special Populations: Older Adults." 14…”
Section: Key Learningsmentioning
confidence: 99%
“…In the same vein, we found that the older adults appreciated opportunities to access information on the Internet and to keep in touch with family. Although use of digital technology and the Internet has increased sharply among older adults in Norway, where 65% of older adults 71 to 80 years of age used the Internet daily in 2018, their adoption of health‐related technologies may still depend on their perceptions of the technology as relevant and useful (Slettemeås et al, 2018; Takemoto et al, 2018). Poor usability experiences (e.g., where entering data is considered to be cumbersome) can negatively influence the sustained use of digital health technology (Wildenbos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Poor usability experiences (e.g., where entering data is considered to be cumbersome) can negatively influence the sustained use of digital health technology (Wildenbos et al, 2018). Older adults can therefore benefit from technology developed especially for their needs regarding both user interface and content (Takemoto et al, 2018). In this way, digital health can be a gateway to technology use for inexperienced users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation